The making of a heretic gender, authority, and the Priscillianist controversy. - Burrus, Virginia (Berkeley University of California press, 1995)
Silenced for 1,600 years, the "heretics" speak for themselves in this account of the Priscillianist controversy that began in fourth-century Spain. In a close examination of rediscovered texts, Virginia Burrus provides an unusual opportunity to explore heresy from the point of view of the followers of Priscillian and to reevaluate the reliability of the historical record. Her analysis takes into account the concepts of gender, authority, and public and private space that informed established religion's response to this early Christian movement.
Keywords: Priscillian, -- Bishop of Avila, -- approximately 350-385.; Priscillianism; Women in Christianity -- Spain -- History -- Early church, ca. 30-600; #GOSA:II.P.PRIS.M; 273.22 -- Priscillianisme